L’expérience de la limite et la manifestation du sens: un voyage mythologique du sens dans Cassandre de Lessia Oukraїnka - Tarasyuk, Yaryna (2022)
The article explores the limit phenomenon in terms of its participation in the process of the formation andtransformation of meanings. The functioning of the concept is considered on the basis of the dramatic poemCassandra by Lesya Ukrainka. Since the work is based on myth and itself imitates the structure of a myth, thusrevealing a noticeable feature of European culture at the turn of the 19th–20th centuries regarding the fundamentaldevelopments of mytho-critical schools, the border phenomenon is illuminated through the prism of two aspects– content and form. The first aspect focuses on existential meanings; it is about the formation or transformationof meanings at the moment a person reaches his limit or the limit of the world (first of all, a meeting with fate ordeath). The second aspect concerns the phenomenon of myth and the manifestation-formation of new meaningsat the moment of interaction between the myth matrix and its literary interpretation. The focus of the analysison the threshold phenomena of Cassandra demonstrates the playwright’s skill in working with the ancient myth.Lesya Ukrainka preserves the outline of the myth and the literary image of the Trojan prophetess, but also inscribesnew meanings that are relevant to her time, thus universalizing them, and revives myth itself as a universal form ofpreserving and transporting meanings
Keywords: limit; boundary situation; meaning formation; meaning transformation; myth; literary interpretation of myth